Nurses’ Self-Care Practices: A Cross-Sectional Study in Philippine District Hospitals - Nobis, Peter Paul Aniversario; Oducado, Ryan Michael Flores (Fakultas Ilmu-ilmu Kesehatan, 2024)
The global risk of morbidity and mortality due to hypertension highlights the importance of optimizing nurses’ roles in controlling hypertension through education. This study aims to develop educational models for patients and families with hypertension. A sequential mixed-method research design was used. Focus group discussions and in-depth interviews were conducted with 28 participants to explore the phenomenon and health education needs of patients and families with hypertension, and the data were analyzed thematically. A survey of 40 people was conducted to identify the elements of a workable model using SEM analysis. The researchers then used an integration matrix to perform the data integration. Seven themes were revealed from the qualitative phase: (1) health problems, (2) scope of educational services, (3) primary service activities, (4) health education methods, (5) information needs, (6) management support, and (7) barriers. The following sub-components were also obtained from the analysis: (1) Health Education Approach, (2) Health Education Program, and (3) Learning Process. The educational model for patients and families with hypertension is complex, and nurses require support to implement such a model. Further research is needed to prove the model’s effect on the personal and interpersonal conditions of hypertensive patients.